Infrared spectroscopy analysis determining secondary structure change in albumin by cerium oxide nanoparticles - Umezawa, Masakazu; Itano, Ryodai; Sakaguchi, Naoya; Kawasaki, Takayasu (Frontiers in Toxicology, 2023)
Cerium oxide (CeO2) nanoparticles are expected to have applications in the biomedical field because of their antioxidative properties. Inorganic nanoparticles interact with proteins at the nanoparticle surface and change their conformation when administered; however, the principle underlying this interaction is still unclear. This study aimed to investigate the secondary structural changes occurring in bovine serum albumin (BSA) mixed with CeO2 nanoparticles having different surface modifications using Fourier transform infrared spectroscopy. CeO2 nanoparticles (diameter: 240 nm) were synthesized from an aqueous cerium (III) nitrate solution using a homogeneous precipitation method. The surfaces of the nanoparticles were modified by the catechol compounds dopamine and 3,4-dihydroxyhydrocinnamic acid (DHCA). In the presence of these CeO2 nanoparticles (0.11–0.43 mg/mL), β-sheet formation of BSA (30 mg/mL) was promoted especially on the amine-modified (positively charged) nanoparticles. The local concentration of BSA on the surface of the positively charged nanoparticles may have resulted in structural changes due to electrostatic and other interactions with BSA. Further investigations of the interaction mechanism between nanoparticles and proteins are expected to lead to the safe biomedical applications of inorganic nanoparticles.